Pengembangan Sistem Ujian Online di Sekolah - Didik Kurniawan; Rico Andrian; Lona Ertina (Universitas Lampung, 2014)
Exam is a test or evaluation that goal is to determine one’s ability. Trials conducted in the school who are generally still conventionally which the implementation is using paper and lasting correction process. The correction process can be facilitated by making the online examination system in school. System development method used is the waterfall method. Process method waterfall in the process is done sequentially. System that superbly produced which is a system that can be accessed by three users are administrators, teachers, and students. Development of online examination system in school to facilitate the teachers in terms of correcting for direct assessment process can get online after the exam is over. This test system is implemented by using database mySql and php programming language.